Defining and quantifying national-level targets, indicators and benchmarks for management of natural resources to achieve the sustainable development goals - Dickens, Chris; Smakhtin, Vladimir U.; McCartney, Matthew P.; O’Brien, G.; Dahir, L. (MDPI, 2019)
The 2030 Agenda for Sustainable Development, the Sustainable Development Goals (SDGs), are high on the agenda for most countries of the world. In its publication of the SDGs, the UN has provided the goals and target descriptions that, if implemented at a country level, would lead towards a sustainable future. The IAEG (InterAgency Expert Group of the SDGs) was tasked with disseminating indicators and methods to countries that can be used to gather data describing the global progress towards sustainability. However, 2030 Agenda leaves it to countries to adopt the targets with each government setting its own national targets guided by the global level of ambition but taking into account national circumstances. At present, guidance on how to go about this is scant but it is clear that the responsibility is with countries to implement and that it is actions at a country level that will determine the success of the SDGs. Reporting on SDGs by country takes on two forms: i) global reporting using prescribed indicator methods and data; ii) National Voluntary Reviews where a country reports on its own progress in more detail but is also able to present data that are more appropriate for the country. For the latter, countries need to be able to adapt the global indicators to fit national priorities and context, thus the global description of an indicator could be reduced to describe only what is relevant to the country. Countries may also, for the National Voluntary Review, use indicators that are unique to the country but nevertheless contribute to measurement of progress towards the global SDG target. Importantly, for those indicators that relate to the security of natural resources security (e.g., water) indicators, there are no prescribed numerical targets/standards or benchmarks. Rather countries will need to set their own benchmarks or standards against which performance can be evaluated. This paper presents a procedure that would enable a country to describe national targets with associated benchmarks that are appropriate for the country. The procedure builds on precedent set in other countries but in particular on a procedure developed for the setting of Resource Quality Objectives in South Africa. The procedure focusses on those SDG targets that are natural resource-security focused, for example, extent of water-related ecosystems (6.6), desertification (15.3) and so forth, because the selection of indicator methods and benchmarks is based on the location of natural resources, their use and present state and how they fit into national strategies.